Impact of E-service quality on brand attachment and willingness to spend more - Gul-e-Rana, Rana; Mohamadali, Noor Azizah; Shah, A.; Muhammad, L (Faculty of Natural Sciences, University of Sindh, 2018)
E-service quality is important in current business practices. This concept is yet to be explored in context of influencing other important variables. This paper aims to conceptualize e-service quality relationship with brand attachment and willingness to spend more. Understanding the relationship between these constructs is important for service providers in order to enhance superior online customer service experience. Suggested linkages amongst variables further need empirical support. Theoretical implications and future research directions are also proposed.